PRODUKSI ANGKAK OLEH Monascus purpureus DENGAN MENGGUNAKAN BEBERAPA VARIETAS PADI YANG BERBEDA TINGKAT KEPULENANNYA - Agus, Purwanto (Widya Warta, 2011)
The preparing of red yeast rice or angkak using strain Monascus purpureus was carried out on various kinds of rice which have differences in their stickiness, namely Cisadane, IR 64, and IR 36. The aim of the research was to know the content of the angkak pigment and the yield of red yeast rice. The red yeast rice product obtained was observed on basis of the intensity of red pigment and yellow pigment. To measure the content of pigment, the angkak powder was extracted by the use of methanol. By using spectrophotometer the content of the pigment could be measured with 390 nm wave lengths for the yellow pigment and 500 nm for the red pigment. Meanwhile, the yield of red yeast rice was evaluated as the yield percentage. The result showed that the highest pigment content for yellow and red pigments was on the IR 36 variety. Among the three rice varieties used, it should be noted that the highest yield of angkak was on IR 36.